Denosumab: a new option in the treatment of bone metastases from urological cancers - Yuasa, Takeshi (Dove Medical Press, 2012)
Bone metastases often create serious clinical problems: they lead to poor performance status due to pathologic fractures, spinal cord compression and intractable pain, commonly referred to as skeletal-related events. The receptor activator of nuclear factor-κB (RANK), the RANK ligand (RANKL), and osteoprotegerin, a decoy receptor for RANK, regulate osteoclastogenesis and may play a key role in bone metastasis. Denosumab (XGEVA; Amgen, Thousand Oaks, CA), a fully human monoclonal antibody that binds to and neutralizes RANKL, inhibits osteoclast function, prevents generalized bone resorption and local bone destruction, and has become a therapeutic option for preventing or delaying first on-study skeletal-related events in various malignancies. In the context of urological cancer, three main Phase III clinical studies have been published in prostate cancer. This article provides a brief overview of the characteristics of bone metastasis in urological cancers, reviews the mechanisms of bone metastasis, including the RANK/RANKL/osteoprotegerin axis, the current standard of care, zoledronic acid, and describes the efficacy of the novel bone-targeted agent denosumab in bone metastasis. Denosumab is emerging as a key therapeutic option in the treatment of bone metastases from urological cancers.